Gula cair dan gula recengan berbahan dasar gula merah tebu - M. Yasser; A.M. Iqbal Akbar Asfar; Marlia Rianti; A.M. Irfan Taufan Asfar; Eko Budianto (Universitas Negeri Makassar, 2020)
This Community Service is a Community Partnership Program that was carried out by to partners of the Brown Sugar Cane Business Group in Latellang Village, Patimpeng District. The processing of sugar cane so far has been very simple, and some of the sugar cane businesses were out of business due to the consumption and need for brown sugar cane by the community, especially the Latellang and other villages, who are reluctant to consume brown sugar cane. This reluctance is caused by the aroma of brown sugar cane. Therefore, diversification of brown sugar cane products was carried out by processing brown sugar cane into Liquid sugar and Recengan sugar. The results of the PKM program were able to provide partners with increased knowledge of processing brown sugar cane into a diversified product that has high economic value and reduced the price of brown sugar cane from Rp. 10,000 per kilogram into products with 250 grams of brown sugar cane as raw material. 2-3 bottles of Liquid Sugar (250 ml plastic packaging) with a price of Rp.10,000 per bottle and produce 15 pieces of Recengan Sugar. Especially for Recengan sugar packaging, it is packaged in pouch containing 8 Recengan sugar ata a price of Rp.10,000. The impact will be revive the production of cane brown sugar to the Cane Brown Sugar Business Group partners, especially in Latellang Village.